2013
DOI: 10.1037/a0035219
|View full text |Cite
|
Sign up to set email alerts
|

Glass ceiling for the foreign born: Perspectives from Asian-born American R&D scientists.

Abstract: In today's globalized economy, more people are migrating to work and live in foreign countries as sojourners or immigrants. Biases against the foreign born can be blatant or subtle. We examined the phenomenon of the glass ceiling, a more subtle form of unequal treatment of the foreign born, for first-generation Asian American scientists in the U.S. pharmaceutical industry, drawing from a study of their career aspirations, strategies, and challenges. Based on in-depth interviews, we identified 4 categories of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Eight studies focused on work and employment. All but one relied on interviews to explore the career aspirations and challenges faced by foreign-born Asian American research and development scientists (Chen, Rao, & Ren, 2013), perceptions of invisibility among Asian American professionals (Sun & Starosta, 2006), and the process of career decision-making in young Chinese Americans (Okubo, Yeh, Lin, Fujita, & Shea, 2007). Other interview studies examined work experiences in the medical field, including gender differences among Asian Indian physicians (Murti, 2012) and the challenges for Filipino physicians who became nurses after migrating to the United States (Vapor & Xu, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies focused on work and employment. All but one relied on interviews to explore the career aspirations and challenges faced by foreign-born Asian American research and development scientists (Chen, Rao, & Ren, 2013), perceptions of invisibility among Asian American professionals (Sun & Starosta, 2006), and the process of career decision-making in young Chinese Americans (Okubo, Yeh, Lin, Fujita, & Shea, 2007). Other interview studies examined work experiences in the medical field, including gender differences among Asian Indian physicians (Murti, 2012) and the challenges for Filipino physicians who became nurses after migrating to the United States (Vapor & Xu, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Reasons for the lack of leadership opportunities are largely unknown. It could be “a matter of personal choice or a pipeline issue” (Sabharwal, 2011a, p. 861) or individual (e.g., language and communication skills) and cultural barriers (e.g., stereotypes and misconceptions) that may hinder their leadership prospects (Chen et al, 2013). Majority of the 29 Asian-born scientists from the Research and Development (R&D) of five pharmaceutical firms who were interviewed in Chen et al (2013) study identified cultural differences as barriers to their career growth.…”
Section: Background Of the Studymentioning
confidence: 99%
“…It could be “a matter of personal choice or a pipeline issue” (Sabharwal, 2011a, p. 861) or individual (e.g., language and communication skills) and cultural barriers (e.g., stereotypes and misconceptions) that may hinder their leadership prospects (Chen et al, 2013). Majority of the 29 Asian-born scientists from the Research and Development (R&D) of five pharmaceutical firms who were interviewed in Chen et al (2013) study identified cultural differences as barriers to their career growth. For example, modesty, which is considered a highly valued virtue in Asian cultures could be interpreted as “a lack of confidence, enthusiasm, or conviction” in U.S. organizations (p. 253).…”
Section: Background Of the Studymentioning
confidence: 99%
“…The latter generally come from more privileged backgrounds and intersect with more educated and higher SES groups on arrival; they are less likely to experience overt discrimination. It makes for a different experience, as is pointed out in Chen and Rao's (2013) article about the initial denial, but later awareness of the glass ceiling among Asian-born American scientists; they learn that the initial respect for their technical expertise does not translate into access to the ranks of leadership, despite career aspirations. Xin (2004) has shown that Asian American managers report using significantly lower levels of self-disclosure, self-focused impression management tactics, and supervisor-focused impression management tactics, but more job-focused impression management tactics compared with European American managers, and has suggested that this explains why Asian Americans are less likely to attain leadership roles.…”
Section: Stereotyped Threat: Perceptions Of Asian American Leadersmentioning
confidence: 99%
“…The latter generally come from more privileged backgrounds and intersect with more educated and higher SES groups on arrival; they are less likely to experience overt discrimination. It makes for a different experience, as is pointed out in Chen and Rao’s (2013) article about the initial denial, but later awareness of the glass ceiling among Asian-born American scientists; they learn that the initial respect for their technical expertise does not translate into access to the ranks of leadership, despite career aspirations.…”
Section: Stereotyped Threat: Perceptions Of Asian American Leadersmentioning
confidence: 99%